Magnitude and controls of N2 fixation in the subtropical Northeast Atlantic - Benavides, Mar (2013)
Programa de doctorado: Oceanografía (bienio 2008-2010) Biological N2 fixation contributes significantly to new production in the oligotrophic subtropical gyres, which cover ~50% of the world’s oceans. It was generally assumed that diazotrophy was restricted to the warm (>20ºC) and stratified surface waters of the tropical and subtropical oceans (<200 m). Nevertheless, recent evidence indicates that diazotrophic organisms are more diverse than it was previously thought, and able to fix N2 at higher latitudes and depths where the temperatures are colder. In the last decade intense research has been devoted to the study of N2 fixation rates and the diversity of diazotrophs in the different oceanic basins of the world. However, most of the studies have beenconcentrated in the western Atlantic Ocean, whereas its eastern half has been seldom studied. In this thesis N2 fixation and dissolved nitrogen release rates, as well as the diversity of diazotrophic organisms over different areas of the subtropical Northeast Atlantic, were studied considering the effect of various environmental factors (e.g. temperature, aerosols, nutrients). We found that N2 fixation rates in the eastern subtropical Atlantic are generally low compared to the western basin, although the eastern subtropical region provides >70% of the N2 fixed in the whole North Atlantic subtropical latitudinal band. Size-‐fractionated experiments showed that unicellular diazotrophs (<10 μm fraction) predominate in these waters, as they typically contributed ~20-‐90% to total N2 fixation. This was further confirmed by whole-‐cell hybridization analyses, which indicated that the predominant diazotrophic forms usually ranged from <1 μm to 3 μm in size. Moreover, analyses of the nifH gene revealed that UCYN-‐A diazotrophs are especially abundant in these waters. The deposition of atmospheric dust over the Canary Islands waters had a differential effect on N2 fixation rates by different groups: the diazotrophic activity of unicellular diazotrophs ...